Effect of peripheral nerve blocks on postanesthesia care unit length of stay in patients undergoing ambulatory surgery: a retrospective cohort study. Issue 3 (15th January 2021) - Polshin, Victor; Petro, Julie; Wachtendorf, Luca J; Hammer, Maximilian; Simopoulos, Thomas; Eikermann, Matthias; Santer, Peter
Abstract : Background: Peripheral regional anesthesia and analgesia may increase the efficiency of ambulatory surgical centers by reducing pain and preventing nausea and vomiting, which are important modifiable causes of prolonged postanesthesia care unit (PACU) length of stay. We hypothesized that the use of peripheral nerve blocks (PNB) was associated with shorter PACU length of stay in ambulatory surgery. Methods: In this retrospective cohort study, we analyzed data from adult ambulatory surgical cases, in which PNB was a viable anesthetic option (ie, was routinely performed for these procedures), at an academic medical center between 2008 and 2018. We assessed the association between the use of PNB and the primary endpoint of PACU length of stay. As key secondary endpoint, we compared intraoperative opioid doses. Analyses were adjusted for patient demographics, comorbidities and intraoperative factors. Results: A total of 57 040 cases were analyzed, of whom 13 648 (23.9%) received a PNB. The use of PNB was associated with shorter PACU length of stay (a decrease of 7.3 min, 95% CI 6.1 to 8.6, p<0.001). This association was most pronounced in surgeries of long duration (decrease of 11.2 min, 95% CI 9.0 to 13.4) and in patients undergoing leg and ankle procedures (decrease of 15.1 min, 95% CI 5.5 to 24.6). Intraoperative opioid doses were significantly lower in patients receiving a nerve block (decrease of 9.40 mg oral morphine equivalents, 95% CI 8.34 to 10.46, p<0.001). Conclusion: The use of PNB significantly reduced PACU length of stay in ambulatory surgical patients, which may in part be attributed to lower intraoperative opioid requirements.